2008
DOI: 10.1371/journal.ppat.1000247
|View full text |Cite
|
Sign up to set email alerts
|

Regulated Nuclear Trafficking of rpL10A Mediated by NIK1 Represents a Defense Strategy of Plant Cells against Virus

Abstract: The NSP-interacting kinase (NIK) receptor-mediated defense pathway has been identified recently as a virulence target of the geminivirus nuclear shuttle protein (NSP). However, the NIK1–NSP interaction does not fit into the elicitor–receptor model of resistance, and hence the molecular mechanism that links this antiviral response to receptor activation remains obscure. Here, we identified a ribosomal protein, rpL10A, as a specific partner and substrate of NIK1 that functions as an immediate downstream effector… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
131
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 117 publications
(137 citation statements)
references
References 46 publications
5
131
0
1
Order By: Relevance
“…We also investigated the infection course of Y10A associated with ␤-WT or its phosphorylation mimic mutants in wild-type N. benthamiana plants, as described previously (27,33). For Y10A/␤-WT inoculation, disease symptoms started to appear at 3 or 4 dpi, with all the plants displaying typical symptoms at 8 to 10 dpi (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We also investigated the infection course of Y10A associated with ␤-WT or its phosphorylation mimic mutants in wild-type N. benthamiana plants, as described previously (27,33). For Y10A/␤-WT inoculation, disease symptoms started to appear at 3 or 4 dpi, with all the plants displaying typical symptoms at 8 to 10 dpi (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The course of viral infection was monitored as described previously (27,33). Total nucleic acids were extracted from systemically infected leaves using a cetyltrimethylammonium bromide (CTAB)-based method (63).…”
Section: Methodsmentioning
confidence: 99%
“…One possibility is that the increased number of nuclear proteins associated to AtRPL10 arises from increased translocation of AtRPL10B to the nucleus after the UV-B treatment. Carvalho et al (2008) previously demonstrated that, after viral infection, AtRPL10A is phosphorylated by the NSP-INTERACTING KINASE1 (NIK1), redirecting the protein to the nucleus, whereas when NIK1 is mutated, RPL10A fails to accumulate in the nucleus. Therefore, a similar situation may occur after UV-B exposure with AtRPL10B, where it may fulfill specific functions in response to this radiation.…”
Section: Discussionmentioning
confidence: 99%
“…To assess the biological significance of SlSnRK1-bC1 interactions in vivo, we inoculated wild-type and transgenic N. benthamiana plants carrying an Arabidopsis antisense SnRK1 expression cassette (AS-12) or an Arabidopsis sense SnRK1 expression cassette (S-5; Hao et al, 2003) with TYLCCNV/TYLCCNB and monitored infection over time (Carvalho et al, 2008b). Changes in SnRK1 expression altered the timing of symptom appearance, with overexpressing plants developing symptoms later and silenced plants showing symptoms earlier than wild-type plants (Fig.…”
Section: Identification Of the Domains Necessary For Bc1 And Slsnrk1mentioning
confidence: 99%
“…Wild-type or transgenic N. benthamiana plants expressing Arabidopsis antisense SnRK1 (AS-12) or Arabidopsis sense SnRK1 (S-5) were agroinoculated with an overnight culture of A. tumefaciens carrying TYLCCNV and TYLCCNB (pBinPLUS-1.7A and pBinPLUS-2b; Cui et al, 2004) or TYLCCNB mutants. The course of infection was monitored as described (Carvalho et al, 2008b). DPI 50% was determined using data from three independent experiments.…”
Section: Virus Inoculation and Infectivity Testsmentioning
confidence: 99%